(untitled) (Principles and Practice of Clinical Research, 2023)
Introduction: Inflammasomes are multiprotein complexes innate to the immune system that, upon activation, initiate a chain reaction culminating in the production of cytokines IL-1 and IL-18. Recent studies have suggested a connection between inflammasome activation and neurological diseases such as multiple sclerosis (MS). In this review, we aimed to evaluate the role of inflammasomes as potential therapeutic agents and prognostic markers of MS. Methods: Through a database search, 156 articles were identified. Of these, we selected articles focusing on observational and interventional studies that either directly measured the expression of inflammasomes or the levels of cytokines or interleukin as outcomes. After applying a snowball sampling strategy, this review ultimately included nine studies. Results: Our search yielded nine studies published between 2010 and 2022—9 observational studies included case-control and cohort designs. All studies comprised adult populations, 20–72 years of age. All studies incorporated a control group. We selected studies that utilized surrogate measures to evaluate outcomes such as inflammasome expression of NLRP3 or similar genes and assess cytokine levels such as IL-1β, IL-18, IL-23, and TNF. Discussion: Overall, the revised studies suggest a possible role for inflammasomes components, including ASC and caspase-1, which have been evaluated as potential prognostic markers in MS. Therapeutic strategies have focused on the inhibition of NLRP3, which is one of the most prominent and studied inflammasomes, by IFN-β.